2011
DOI: 10.1103/physreva.83.063617
|View full text |Cite
|
Sign up to set email alerts
|

Tunable dipolar resonances and Einstein-de Haas effect in aRb87-atom condensate

Abstract: We theoretically study a spinor condensate of 87 Rb atoms in a F = 1 hyperfine state confined in an optical dipole trap. Putting initially all atoms in an m F = 1, component we observe a significant transfer of atoms to other, initially empty Zeeman states exclusively due to dipolar forces. Because of conservation of a total angular momentum the atoms going to other Zeeman components acquire an orbital angular momentum and circulate around the center of the trap. This is a realization of the Einstein-de Haas e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
(38 reference statements)
0
24
0
Order By: Relevance
“…In the system composed of 52 Cr atoms [25][26][27][28] Feshbach resonances can enhance the effect of dipole-dipole forces. It was suggested in [29][30][31][32][33], and confirmed in [34], that dipolar effects may be observed also in the spinor F = 1 87 Rb BEC. The existence of long-range interactions is a motivating factor for studing systematically the effect of dipolar interactions on the level of squeezing in the simplest F = 1 spinor BECs.…”
Section: Introductionmentioning
confidence: 98%
“…In the system composed of 52 Cr atoms [25][26][27][28] Feshbach resonances can enhance the effect of dipole-dipole forces. It was suggested in [29][30][31][32][33], and confirmed in [34], that dipolar effects may be observed also in the spinor F = 1 87 Rb BEC. The existence of long-range interactions is a motivating factor for studing systematically the effect of dipolar interactions on the level of squeezing in the simplest F = 1 spinor BECs.…”
Section: Introductionmentioning
confidence: 98%
“…Magnetic interactions can lead to a transfer of angular momentum from spin to orbital degrees of freedom. This phenomenon, discovered in ferromagnetic solid samples, is known as the Einstein-de Haas effect [9][10][11][12]. Not a long range character of magnetic dipolar interactions but rather their relation to the angular momentum plays a crucial role in this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…This energy is typically much larger than the energy of dipolar interactions and conservation of energy strongly suppresses the spin dynamics. The transfer of atoms between two spinor components can be enhanced by tuning energies of states involved via Zeeman effect [11]. We extend this idea to lattice gases.…”
Section: Introductionmentioning
confidence: 99%
“…In axially symmetric traps the phase of the m S = 2 atoms' wavefunction displays a characteristics vortex-like defect signifying an orbital angular momentum in a final state. This scenario has been studied in the mean field limit, for a three component Rubidium spinor condensate [8]. It has been shown that different final states, all involving vortex-like excitation, can be populated via the dipolar processes of the EdH type.…”
Section: Introductionmentioning
confidence: 99%